Productivity and linkages of the food web of the southern region of the western Antarctic Peninsula continental shelf - Ballerini, Tosca (2014)
The productivity and linkages in the food web of the southern region of the west Antarctic Peninsula continental shelf were investigated using a multi-trophic level mass balance model. Data collected during the Southern Ocean Global Ocean Ecosystem Dynamics field program were combined with data from the literature on the abundance and diet composition of zooplankton, fish, seabirds and marine mammals to calculate energy flows in the food web and to infer the overall food web structure at the annual level. Sensitivity analyses investigated the effects of variability in growth and biomass of Antarctic krill (Euphausia superba) and in the biomass of Antarctic krill predators on the structure and energy fluxes in the food web. Scenario simulations provided insights into the potential responses of the food web to a reduced contribution of large phytoplankton (diatom) production to total primary production, and to reduced consumption of primary production by Antarctic krill and mesozooplankton coincident with increased consumption by microzooplankton and salps. Model-derived estimates of primary production were 187-207gCm-2y-1, which are consistent with observed values (47-351gCm-2y-1). Simulations showed that Antarctic krill provide the majority of energy needed to sustain seabird and marine mammal production, thereby exerting a bottom-up control on higher trophic level predators. Energy transfer to top predators via mesozooplanton was a less efficient pathway, and salps were a production loss pathway because little of the primary production they consumed was passed to higher trophic levels. Increased predominance of small phytoplankton (nanoflagellates and cryptophytes) reduced the production of Antarctic krill and of its predators, including seabirds and seals.